2007
DOI: 10.1210/jc.2007-0476
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Testing for Mutations in theMEN1Gene in Sweden: A Report on 200 Unrelated Cases

Abstract: A total of 4% of all mutations were large deletions, and MLPA is now included in our standard MEN1 mutation screening. Individuals with at least one typical endocrine tumour and at least one of the following: 1) a first-degree relative with a major endocrine tumor; 2) an age of onset less than 30 yr; and/or 3) multiple pancreatic tumors/parathyroid hyperplasia were most likely to harbor a mutation; thus these patients should be screened for MEN1 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
90
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 28 publications
16
90
1
1
Order By: Relevance
“…It is well accepted that pediatric MEN1 patients usually present fewer MEN1-related tumors than adults. However, as observed in our patient cohort and in others reported previously, the full manifestation of the disease (with the development of all four of the main MEN1-related tumors) does not occur in every adult patient older than 30 years (9,10,19,20,22,23,24,25). In fact, we found that age was not a risk factor for developing multiple tumors in three or four glands among our patients aged 30 years or more (PZ0.70).…”
Section: Phenotypic Modulation Of Rs2066827 In Men1 Overall Cohortsupporting
confidence: 81%
“…It is well accepted that pediatric MEN1 patients usually present fewer MEN1-related tumors than adults. However, as observed in our patient cohort and in others reported previously, the full manifestation of the disease (with the development of all four of the main MEN1-related tumors) does not occur in every adult patient older than 30 years (9,10,19,20,22,23,24,25). In fact, we found that age was not a risk factor for developing multiple tumors in three or four glands among our patients aged 30 years or more (PZ0.70).…”
Section: Phenotypic Modulation Of Rs2066827 In Men1 Overall Cohortsupporting
confidence: 81%
“…(2,3) Since then, approximately 500 different germline mutations that cause loss of MEN1 gene function have been identified in patients with MEN1 and related disorders. (4)(5)(6)(7)(8)(9)(10) The germline mutations are heterozygous, and somatic loss of the normal MEN1 allele has been observed in the tumors arising in MEN1, in agreement with the Knudson's two-hit model. (11) Somatic inactivation of both MEN1 alleles has also been detected in some sporadic endocrine tumors, indicating involvement of this gene in the development of sporadic tumors.…”
supporting
confidence: 73%
“…The mouse menin cDNA was obtained by PCR amplification using a spleen cDNA library as the template as previously described. (15) The previously reported variant sequences and their corresponding phenotypes were according to the references as follows: P12L, L22R, K119del, H139D, A160P, A242V, A309P, T344R, E363del, W436R and R460X; (16) G28A; (17) D153V and A411P; (18) G156C, F364C and F447L; (19) A160T and D418N; (20) R171W and E366D; (21) V184E; (9) T197I and Y353del; (22) W220L and Y351N; (23) R229L; (24) S253W and E274A; (11) E255K; (10) Q260P; (25) L264P and L267P; (26) P277H; (27) G305D; (12) H317Y; (14) P320R; (28) P320L; (29) L414del; (30) and S555N. (31) The expression vector pCMV-BICEP-4 (Sigma, St. Louis, MO, USA), designed to allow translation of two proteins from one bicistronic mRNA, was used for transient co-expression of N-terminal FLAG-tagged and Myc-tagged menin proteins.…”
Section: Methodsmentioning
confidence: 99%